2016
DOI: 10.1089/met.2015.0067
|View full text |Cite
|
Sign up to set email alerts
|

C-Peptide Is a Sensitive Indicator for the Diagnosis of Metabolic Syndrome in Subjects from Central Mexico

Abstract: C-peptide is a strong indicator of MetS. Since C-peptide has recently emerged as a biomolecule with significant importance for inflammatory diseases, monitoring C-peptide levels will aid clinicians in preventing MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
2
16
0
4
Order By: Relevance
“…It could be used to represent endogenous insulin secretion by islet β cells and insulin resistance . Studies have found that C‐peptide is significantly associated with NAFLD, being one of the three most important predictors in the general US population, as well as potential risk factors and outcomes of NAFLD, such as cardiovascular diseases and MetS . However, rather limited studies have measured the association between C‐peptide and advanced NAFLD stages.…”
Section: Introductionmentioning
confidence: 99%
“…It could be used to represent endogenous insulin secretion by islet β cells and insulin resistance . Studies have found that C‐peptide is significantly associated with NAFLD, being one of the three most important predictors in the general US population, as well as potential risk factors and outcomes of NAFLD, such as cardiovascular diseases and MetS . However, rather limited studies have measured the association between C‐peptide and advanced NAFLD stages.…”
Section: Introductionmentioning
confidence: 99%
“…Encontramos también un aumento significativo de la insulina, con lo que confirmamos el estado hiperinsulinémico de los pacientes con SM+, los mismos hallazgos que fueron descritos por otros autores que obtuvieron resultados similares 32,33 . Además del estado hiperfuncionante secundario al estado de insulinorresistencia, debemos mencionar que el aumento de los niveles de insulina en nuestra población podría ser a su vez potenciado por el uso de medicamentos secretagogos de insulina en la población SM+, efecto que ya se ha corroborado principalmente en los pacientes bajo tratamiento con sulfonilureas.…”
Section: Discussionunclassified
“…Según artículos, en pacientes con SM y en individuos obesos las concentraciones plasmáticas de amilina suelen estar incrementadas; misma situación se encuentra en nuestro estudio donde se aprecian niveles de amilina mayores en pacientes con SM+ en contraste con los SM-(9.9 ± 0.6 vs. 7.8 ± 0.5, pmol/l; p < 0.05) 32,[37][38][39] .…”
Section: Discussionunclassified
“…In a large community-based survey of adults in china, was conducted by the Yang-Ming Crusade in 1992 and 1994 among a total of 1,447 men and 1,800 women (mean age 46.7 years), found that fasting C-peptide was significantly higher among hypertensive subjects in comparison to normotensives (p= 0.00) 22 .…”
Section: Discussionmentioning
confidence: 99%